Effectiveness of Aspergillus oryzae fermentation culture to improve digestion of fibrous feeds - Darwinsyah Lubis; E Wina; B Haryanto; T Suhargiantatmo (Indonesian Center for Animal Research and Development (ICARD), 2002)
Studies regarding the use of living microorganisms as supplement have been done in the last two decades to improve digestion process in the rumen. Many factors affect the use of the supplement, such as ration composition and physiological status of the animals. Materials used in this experiment are Aspergillus oryzae (AO) derived from ‘tauco’ (salty fermented soybean) and soybean sauce processing factories located in Bogor, Cianjur, and Sukabumi districts (15 sources), and also AO culture collections of the Indonesian Res. Inst. for Anim. Prod. (2 strains) and one strain from Indonesian Res. Inst. for Vet. Sci. in Bogor. The fungus was first isolated in potato dextrose agar (PDA), incubated at room temp. (26-300C) for 5 days for purification. The AO from PDA then inoculated into cooked rice enriched with mineral mix, oven-dried (40-450C), then ground and kept in refrigerator as a stock culture for further use. To produce more AO (scaling-up), the culture is inoculated in two basal media, i.e. soybean meal and ‘onggok’ (tapioca processing waste) enriched with mineral mix, dried and ground, then kept in refrigerator as A. oryzae fermentation culture (AOFC). Ground-dried King grass was used for in vitro digestion trials using sheep rumen fluid, which was not supplemented (control) or supplemented with the AOFC (10% w/w) from various sources. Three best AOFC (by origin) were chosen and used for further digestion study. The study was run using 2 (media) x 3 (AOFC origin) factorial experiment based on a completely randomized design and Duncan’s MRT was applied to test differences among treatment means. Preliminary results indicated of the AOFC-SP66, -F172, and -CT4 used, the best AOFC was SP66, as it increased (P<0.05) fiber (NDF) digestion (10.5% better than the control). Total VFA productions were similar, but acetate content in the rumen fluid was lowered (P<0.05), while propionate and butyrate levels were alleviated (P<0.05) by the AOFC-SP66. Ammonia content was not affected by addition of AOFC. No differences were detected on digestion parameters between the two media used for AO cultivation, therefore, it is suggested to use ‘onggok’ for producing AOFC in large scale. VFAs composition pattern suggests that AOFC was more suitably used for meat rather than for milk production. Key words: Fungus, King grass, digestibility, rumen fluid